O modelo de desenvolvimento do Polo Industrial de Manaus e a discussão sobre a segurança jurídica - Pontes, Rosa Oliveira de (2011)
The study of the Manaus Industrial Hub development model is important for its representativeness for the State of Amazonas and repercussion within the context of the Amazon region. This dissertation reviews this regional promotional policy through several perspectives with the purpose of shedding some light onto performed stages and the mechanisms applied in its evolution, pitching it against the legal security, an indispensable element for a Law-abiding Democratic State. The study starts off from a rereading of the theories underpinning the conceptual evolution of development both from the interdisciplinary standpoint of the economy, the history and of the economic law giving priority to those which directly or indirectly have influenced the conceptual basis of the Manaus Industrial Hub and showing the new dimensions, highlighting the issue of socioenvironmental sustainability, intrinsically applicable to the Amazon reality. As a whole, the main phases of the national development as sequenced starting from the thirties of the XX century the when the Brazilian State began to adopt developmental strategies until these days, emphasizing political and economic aspects, which have interfered in the readequability of the original proposal and have produced its current conformation, with a brief historical description the public policies, which have intended to interfere in the economic and industrial performance of the Amazon space resulting in the creation of the Manaus Free Trade Zone (ZFM) and of the Manaus Industrial Hub (PIM). The text puts forward some reflections on its main phases, contradictions, difficulties and perspectives and the repercussions resulting from the regulatory alterations at all levels, to, at the end, promote a study of the main constitutional and tributary focuses of the issue giving priority to the theme of legal security, probing into its real existence and effectiveness.